(untitled) (Journal of the College of Basic Education, 2024)
The research aims to examine the effect of internal and external strategies on the achievement of science subjects in Al-Safa Al-Khamis primary school, achieving the research objective of the National Freedom Institutions: ) There is no difference between the two statistical means. The level (0.05) is found between the mean means of the experimental group that studies the love of life on internal and external transformations and the studies of the library groups that study the same means on internal and external strategic alliances. The chopsticks method with academic experience) After the experimental design of the experimental and administrative group for Al-Badaiyat News for Attainment, the analytical research conducted on government primary schools today, in Sulaymaniyah Governorate, for the academic year 2023/2024, and Muharik Bah is the primary school presented. The Ministries of Education in Sulaymaniyah for the academic year 2023/2024, and there are gestures to implement experimentation and research (60) plots of land for experimentation groups on teaching strategies outside and outside the field, and (30) plots of progress for the textbook groups taught in a two-day method, and the results of the research are sufficient. In the research group before the innovations with experiences in the avant-garde variables (temporal age, correspondences, achievement, and laughter), dedicating educational subjects to specialists for teaching the first and second units of pedagogy, the ornaments to me, the words of the pure, Thursday, the day, and the researcher’s difficulty (119) Al-Khalawi, updating the giving of the classification of flowers to the cognitive field and the five equations (mnemonic, Synthetic, applied, tahlili, compositions)) Complete search for professions. Topics for more than (30) professions for professions in the first academic world of the academic world (2023/2024), which are releases for three sub-sections and the group association. With the help of Alaa, the results of the researcher are as follows: 1- Teaching Al-Safi Al-Khamis primary school and the internal and external strategic guitar in an impressive manner in Rafi, the Encyclopedia of Education, Lada. Students in the experimental groups compete with the internal and external sections. Alaa Al-Din Al-Dubaat group training, studying chopsticks. 2- It provides internal and external strategic teaching and education for two equal knights to coordinate through their positive participation in the activities of the house and the individual group’s initiatives. Based on this research, there are a number of explanations and solutions in the spring semester.